Electronic waste bank model as a solution for implementing circular economy: Case study DKI Jakarta-Indonesia - Rimantho, Dino; Syaiful, Syaiful; Nurfaida,; Sulandari, Uci (Frontiers in Built Environment, 2022)
Indonesia currently does not use a systematic method of managing electronic waste (e-waste). The informal sector handles e-waste mostly without regard to the environment or public health. Establishing a national collection system favored by the community is the most challenging problem. Even though the waste bank system (WB) does not collect e-waste, it can provide a solution because it is well known as a recycling program by Indonesian citizens. This study proposes a WB system model for e-waste collection to interact with other stakeholders in DKI Jakarta, Field research and interviews with several essential informants were conducted. E-waste samples were identified to determine the composition of the current management and proposed an e-waste bank model as a sustainable circular economy implementation. E-waste has enormous potential for recycling, but it also has hazardous materials if not recycled properly. The government must make national regulations on e-waste management and develop cooperation between local governments, industry/producers, recycling industries, and the community to build a WB-based e-waste collection system.